Mitochondrial Protection by Exogenous Otx2 in Mouse Retinal Neurons - Hyoung-Tai Kim; Soung Jung Kim; Young-In Sohn; Sun-Sook Paik; Romain Caplette; Manuel Simonutti; Kyeong Hwan Moon; Eun Jung Lee; Kwang Wook Min; Mi Jeong Kim; Dong-Gi Lee; Antonio Simeone; et al. (Cell Reports, 2015)
OTX2 (orthodenticle homeobox 2) haplodeficiency causes diverse defects in mammalian visual systems ranging from retinal dysfunction to anophthalmia. We find that the retinal dystrophy of Otx2+/GFP heterozygous knockin mice is mainly due to the loss of bipolar cells and consequent deficits in retinal activity. Among bipolar cell types, OFF-cone bipolar subsets, which lack autonomous Otx2 gene expression but receive Otx2 proteins from photoreceptors, degenerate most rapidly in Otx2+/GFP mouse retinas, suggesting a neuroprotective effect of the imported Otx2 protein. In support of this hypothesis, retinal dystrophy in Otx2+/GFP mice is prevented by intraocular injection of Otx2 protein, which localizes to the mitochondria of bipolar cells and facilitates ATP synthesis as a part of mitochondrial ATP synthase complex. Taken together, our findings demonstrate a mitochondrial function for Otx2 and suggest a potential therapeutic application of OTX2 protein delivery in human retinal dystrophy.